Individual Differences in Working Memory Capacity and Dual-Process Theories of the Mind. [ Articles]. - Barret, Lisa Feldman
Dual-process theories of the mind are obiquitous in psychology. A central of these theories is that behavior is determined by the interplay of automatic and controlled processing. In this article, the authors examine individual differences in the capacity control to control attention as a major contributor to differences in working memory capacity (WMC) . The authors discuss the enormous implication of this individual difference for a host of dual-process theories in social, personality, cognitive, and clinical psychology. In addition, the authors purpose several new areas of investigation that derived directly from applying the concept of WMC to dual -process theories of the mind. -- (from the author)